Implementation of pharmacist-led tele medication management clinic in ambulatory care settings: A patient-centered care model in COVID-19 Era - Syed Iqbal Mohiuddin (Elsevier, 2021)
Over the past 20 years, owing to rapid advances in technological innovation, namely in telecommunication and telemedicine, healthcare institutions have integrated clinical practices with cutting-edge telecommunication technology to enhance access to patient care, improve continuity of clinical care, and ensure patient safety. Johns Hopkins Aramco Healthcare (JHAH) is a gold-certified tertiary care institution, and it is an excellent center for patient-centered care. In response to the Coronavirus 2019 (COVID-19) pandemic, it has adopted various telecommunication technologies to provide patient-care services. This article describes the integration of telecommunication technology, such as telephone and video consultation, with a pharmacist-led medication management clinic (MMC) to provide person-centered patient care services at JHAH. The JHAH pharmacy services were found to be essential in establishing face-to-face outcome-oriented pharmacist-led medication management services for patients requiring chronic ambulatory care. The established tele-MMC services enhanced patient engagement and treatment compliance, and the integration process and its challenges were assessed. Especially during this COVID-19 pandemic, the pharmacist-led tele-MMC services were beneficial to chronic disease patients and ensured the continuity of care, maintenance of up-to-date lab tests, management of polypharmacy, minimization of the use of unwanted medications and medication synchronization. Further, the pharmacist-led tele-MMC services provided comprehensive patient counseling, which included the use of visual aids. This new integrated model provides an example for other healthcare organizations to adopt and implement the program in ambulatory care settings, to better ensure the continuity of quality healthcare, especially for elderly patients and those with chronic diseases.